(untitled) (Studia Prawnicze / The Legal Studies, 1981)
Similarily to other highly developed countries of the West, also in the United States of America the tendency to widen economic and social functions of state has been continuously strengthened during this century and particularity beginn- ing with the World War Two. However, this tendency meets certain barriers resulting both from the conviction that freemarket economy is superior to pla- nified economy (even if only partially so), and from the structure of the whole system of institutions of political power which follows the principles of eco- nomic “laissez faire”. Federal structure of the state is an additional restraint here, as well as the anxiety of the states to preserve their powers. Considering the above circumstances it seems understandable - and that is the main theses of this article - that presidency became the main institution to realize “welfare state”. Taking into account president’s duty to care for social peace, his lower aptness to pressures of particular groups of interests and responsibility for military and foreign policy, the president is most interested in developing state interventionism. This often was and still now is the reason of many president’s conflicts with the Supreme Court and the Congress. In these conflicts position taken by the president is often closer to the position reflecting general interests, which in american conditions means safeguarding, the system as a whole and creating conditions for its reproduction. On the other hand the Congress which subjects itself to egoistic attitudes of its representatives, more often reconciles fragmentary and temporary interests of particular groups of capital. Valuation of these phenomena is complicated because on the one hand it must take into account the intention to stabilize capitalism, and on the other - it cannot ignore certain postulates of the working masses consedered in general interest. Obviously, provisions of the constitution which defines competences of state organs, do not consider present scale of economic interventionism of federal authorities and that is why specific actions of the president require specific interpretation. However, this intensifies the danger of antidemocratic deformations of the constitutionally established system of exercise of power.